Electrostatic discharge (ESD) improvement to reduce customer complaint - Rahman, Muhd Ambri; Abdul Aziz, Faieza (Academic Journals, 2010)
Electrostatic discharge (ESD) / electrical over stress (EOS) factors cannot be avoided when an organization running daily manufacturing activity. ESD problems are increasing in the electronics industry because of the trends toward higher speed and smaller device sizes which normally these devices are easy to be damaged by ESD. One of the manufacturing company in Malaysia which produces car radio is also facing the same problem. The failure trend related to ESD is become an alarming condition at 0 km (the product still at automotive customer assembly - 0 mileages which the vehicle is not yet sell to end user). In this study, the problem related to ESD and improvement to reduce the failure were conducted. These includes improvements in ESD protection and control which minimize yield losses and 0 km failures, and maintain the company reputation as a supplier of high-quality and reliable products. Findings from this study showed that virtually all materials, even conductors, can be triboelectrically charges. The level of charge is affected by material, speed of contact, separation and humidity. Electrostatic discharge can occur throughout the manufacturing test, handling and operational process. The improvement activity consist of two phases which is 3rd quarter 2009 (July – September) and 4th quarter 2009 (October – November). This followed by the continuous improvement activity take place on the 1st quarter 2010 (January – March). With this improvement, failure trend at customer related to ESD showed a reducing pattern.